Noninvasive characterization of peripheral sympathetic activation across sensory stimuli using a peripheral arterial stiffness index - Xu, Ziqiang; Anai, Reiji; Hirano, Harutoyo; Soh, Zu; Tsuji, Toshio (Frontiers in Physiology, 2024)
The peripheral arterial stiffness index has been proposed and validated as a noninvasive measure quantifying stimulus intensity based on amplitude changes induced by sympathetic innervation of vascular tone. However, its temporal response characteristics remain unclear, thus hindering continuous and accurate monitoring of the dynamic process of sympathetic activation. This paper presents a study aimed at modeling the transient response of the index across sensory stimuli to characterize the corresponding peripheral sympathetic activation. The index was measured using a continuous arterial pressure monitor and a pulse oximeter during experiments with local pain and local cooling stimuli designed to elicit different patterns of sympathetic activation. The corresponding response of the index was modeled to clarify its transient response characteristics across stimuli. The constructed transfer function accurately depicted the transient response of the index to local pain and local cooling stimuli (Fit percentage: 78.4±11.00% and 79.92±8.79%). Differences in dead time (1.17±0.67 and 0.99±0.56 s, p=0.082), peak time (2.89±0.81 and 2.64±0.68 s, p=0.006), and rise time (1.81±0.50 and 1.65±0.48 s, p=0.020) revealed different response patterns of the index across stimuli. The index also accurately characterized similar vasomotor velocities at different normalized peak amplitudes (0.19±0.16 and 0.16±0.19 a.u., p=0.007). Our findings flesh out the characterization of peripheral arterial stiffness index responses to different sensory stimuli and demonstrate its validity in characterizing peripheral sympathetic activation. This study valorizes a noninvasive method to characterize peripheral sympathetic activation, with the potential to use this index to continuously and accurately track sympathetic activators.